Effect of Alcalase Modification of Yellow Lupin (Lupinus luteus L.) Protein Isolate on Some Functional Properties and Antioxidant Activity - Iwona Tesarowicz; Agnieszka Zawiślak; Ireneusz Maciejaszek; Krzysztof Surówka (International Journal of Food Science)
Protein isolate obtained from sweet yellow lupin (Lupinus luteus L.) and its Alcalase hydrolysates were examined for their functional and antioxidant properties in relation to surface hydrophobicity of proteins and peptides and molecular weight distribution. Enzymatic hydrolysis improved the foaming characteristics of lupin proteins, while the emulsifying properties deteriorated. It means that good foaming properties of preparations are determined by the presence of low-molecular δ conglutin and small subunits of γ conglutins. In turn, larger proteins such as α and β conglutin are responsible for maintaining good emulsifying properties. The measured surface hydrophobicity was consistent with the results of emulsifying properties. It has also been shown that the scope of changes in antioxidant properties due to hydrolysis, measured by DPPH method and as reducing power, is more pronounced than with the use of ABTS and FRAP methods.